Numerical Modelling of Molten Carbonate Fuel Cell: Effects of Gas Flow Direction in Anode and Cathode - Tay, Chen Lim; Law, Ming (University Putra Malaysia Press, 2014)
The modelling of a three-dimensional (3-D) molten carbonate fuel cell (MCFC) was developed to study the effects of gas flow direction (co-flow and counter-flow) in anode and cathode on the generated power density by solving the mass and momentum conservation equations, electrochemical reaction and heat transfer. The simulation result of the co-flow temperature distribution was compared with the experimental data obtained from open literature. The molar fraction distribution of gases in the anode and cathode gas channels and temperature distribution across the cell were compared between two different flow directions. Furthermore, the performance of MCFC, which operates in the temperature range of 823 - 1023 K, was analysed by comparing the generated power density. The results showed that MCFC with co-flow attained higher power density compared to that of counter-flow at 873 K. However, at higher temperature of 1023 K, the generated power density was the same for both gas flow directions.